Determinasi Pertumbuhan UMKM: Studi Kasus Kota Tegal - Rozi Fery Setiyaningsih; Mohammad Alfian (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2025)
This research was conducted to examine the impact of e-commerce platform utilization and product quality on the development of Micro, Small, and Medium-sized Enterprises (MSMEs). A quantitative descriptive approach was applied, using multiple linear regression analysis. Data was collected from vendors operating in Pasar Pagi, Tegal City. The research findings indicate that both the adoption of e-commerce and the maintenance of product quality significantly influence MSME advancement. Based on these results, it is highly recommended that MSME actors increase their optimization of e-commerce usage, accompanied by continuous efforts to uphold product quality, in order to drive further business growth.